Decision Support System Analysis as a Recommendation for the Program Keluarga Harapan (PKH) Using a Decision Table in Pematang Serai Village - Zulham Sitorus; Fahmi Kurniawan; Eko Hariyanto; Sandi Afrizal (Bulletin of Information Technology (BIT), 2024)
The Pematang Serai Village Office is a government institution responsible for addressing various issues in the village, including providing aid to the community. The office frequently organizes social programs, such as distributing financial aid to underprivileged residents. However, in managing these funds, problems often arise, such as aid recipients not being properly targeted and the manual process of collecting the required documentation. Additionally, when creating reports, staff must manually go through the files one by one. Each condition selected will have two possible outcomes: fulfilled or not fulfilled. If x conditions are selected, there will be N possible outcomes, calculated as N = 2^n. The rule above shows that columns 17 through 64 no longer affect the decision to provide aid, so those columns can be removed. This writing aims to develop an application that simplifies the process of calculating beneficiaries and distributing aid in Pematang Serai Village, making aid management more organized. The development method used is the Decision Table Method, with system requirements analysis conducted through observation and interviews. The system design is documented using UML (Unified Modeling Language). The results of this research are implemented in a web-based system, which will make the management of financial aid more effective. .